Ulinastatin decreases permeability of blood--brain barrier by inhibiting expression of MMP-9 and t-PA in postoperative aged rats. (3rd May 2016) - Ma, Li; Zhang, Hui; Liu, Yong-zhe; Yin, Yan-ling; Ma, Ya-qun; Zhang, Sheng-suo
Abstract : Tissue-type plasminogen activator (t-PA) and matrix metalloproteinase-9 (MMP-9) have been reported to play important roles in increased permeability of blood–brain barrier (BBB) under many pathological circumstances. We have showed that Ulinastatin, a broad-spectrum serine protease inhibitor, could alleviate inflammation in the hippocampus of aged rats following partial hepatectomy. In this study, we investigate the expression and potential roles of t-PA and MMP-9 in the protective effect of Ulinastatin. We found that partial hepatectomy increased Evans blue leakage in hippocampus at day 1 and 3 postoperatively. Furthermore, surgery decreased the protein levels of claudin-5, ZO-1, and NF-kB p65 while upregulating the mRNA and protein levels of t-PA and MMP-9 in brain capillaries. All these effects caused by surgery were partially reversed by administering Ulinastatin. Our study sheds light on the roles of t-PA and MMP-9 of BBB in post-surgical neuroinflammation and postoperative cognitive dysfunction. Besides, it could also help to understand the mechanism of Ulinastatin alleviating neuroinflammation.